Mobile Application for Student to Learn English Delivered in Malay Language - Mohd Rizal, Ernie Anira; Ariffin, Asma Hanee; Mansor, Marzita; Sulaiman, Suliana; Abdul Wahid, Rohaizah (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Mobile learning or we can simply refertom learning is aprocess of learning via the internet network using mobile devices like smartphones, tablets, laptops, and a lot more. M-learning has increasingly become a popular trend around the globe. Moreover, Learning English is skill-based learning that requires various approaches and techniques. So, the use of technology like mobile applications is the latest solution to solve the challenges of learning English. The study aims to develop a mobile application for students to learn English grammar but delivere din our mother tongue language which is the Malay language. The application helps students learn in their leisure time with out the presence of their teacher. The software development methodology that will beused in this research is the incremental model.